High‐throughput sequencing data clarify evolutionary relationships among North American Vitis species and improve identification in USDA Vitis germplasm collections. Issue 2 (12th March 2018) - Klein, Laura L.; Miller, Allison J.; Ciotir, Claudia; Hyma, Katie; Uribe‐Convers, Simon; Londo, Jason
Abstract : Premise Of The Study: Grapes are one of the most economically important berry crops worldwide, with the vast majority of production derived from the domesticated Eurasian species Vitis vinifera . Expansion of production into new areas, development of new cultivars, and concerns about adapting grapevines for changing climates necessitate the use of wild grapevine species in breeding programs. Diversity within Vitis has long been a topic of study; however, questions remain regarding relationships between species. Furthermore, the identity of some living accessions is unclear. Methods: This study generated 11, 020 single nucleotide polymorphism (SNP) markers for more than 300 accessions in the USDA‐ARS grape germplasm repository using genotyping‐by‐sequencing. Resulting data sets were used to reconstruct evolutionary relationships among several North American and Eurasian Vitis species, and to suggest taxonomic labels for previously unidentified and misidentified germplasm accessions based on genetic distance. Key Results: Maximum likelihood analyses of SNP data support the monophyly of Vitis, subg. Vitis, a Eurasian subg. Vitis clade, and a North American subg. Vitis clade. Data delineate species groups within North America. In addition, analysis of genetic distance suggested taxonomic identities for 20 previously unidentified Vitis accessions and for 28 putatively misidentified accessions. Conclusions: This work advances understanding of Vitis evolutionary relationships and provides the foundation for ongoing germplasm enhancement. It supports conservation and breeding efforts by contributing to a growing genetic framework for identifying novel genetic variation and for incorporating new, unsampled populations into the germplasm repository system.